If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -1) = (3x) + (2x + 1) Reorder the terms: (-1 + 6x) = (3x) + (2x + 1) Remove parenthesis around (-1 + 6x) -1 + 6x = (3x) + (2x + 1) Reorder the terms: -1 + 6x = (3x) + (1 + 2x) Remove parenthesis around (1 + 2x) -1 + 6x = (3x) + 1 + 2x Reorder the terms: -1 + 6x = 1 + (3x) + 2x Combine like terms: (3x) + 2x = 5x -1 + 6x = 1 + 5x Solving -1 + 6x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -1 + 6x + -5x = 1 + 5x + -5x Combine like terms: 6x + -5x = 1x -1 + 1x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 -1 + 1x = 1 + 0 -1 + 1x = 1 Add '1' to each side of the equation. -1 + 1 + 1x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = 1 + 1 1x = 1 + 1 Combine like terms: 1 + 1 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 3x+x-20=220 | | 9x+3x=48 | | -30=-4(x+6)+6(-7x-1) | | 5n-3+10+7n=0 | | 7=5(2x-3) | | 4+6(6-m)=4 | | 22x^2+20x+4=0 | | 8=z+32 | | (K+N)M=r | | 3m^2+19m+26=0 | | 9x-3x+2=x-8+10 | | 1.5x+x+90=180 | | -7(4n+3)+8n=-7n+31 | | 26+8n=6n-2(5-7n) | | 180a+360=540 | | -16+(x-4)=3 | | 2.5whenm=10 | | 3x/5-2=7x/8+20 | | 2x-(4x-9)=27 | | -6n+38=-4(-2+4n) | | 7x+4y=21.25 | | -6x+2(3x-16)=18 | | 12x+22x=66+24 | | 3x-13y=29 | | 2.4c-2=.4(1+6C) | | 9[5-(-4x-6)]=72x+153 | | 3(5x-8)=6x-24 | | 2z+4=3x-1 | | 3(-7x+2)=6 | | 39+2v=-3-4(4v-6) | | 8(y-3)+8=4(y+12) | | y=2w^2+w+3 |